One-pot pseudo five-component synthesis and antioxidant evaluation of 4,4’-(aryl-methylene)bis(3-methyl-1-phenyl-1H-pyrazol-5-ol) - Gouda, Moustafa Ahmed; Al‐Balawi, Majed Musallam Mutlaq; Abu-Hashem, Ameen Ali (European Journal of Chemistry, 2016)
A simple method for the synthesis of some 4,4’-(aryl-methylene)bis(3-methyl-1H-pyrazol-5-ol) derivatives via a one-pot pseudo five-component reaction of phenyl hydrazine, ethyl acetoacetate and aldehydes in acetic acid is reported. The prepared compounds were characterized by elemental analyses and spectral data. Some of the synthesized compounds were screened for their antioxidant activity using 2,2’-azino-bis(3-ethyl benzothiazoline-6-sulfonic acid (ABTS) method; all the investigated compounds showed similar and higher antioxidant activity than ascorbic acid and exhibited high protection against DNA damage induced by the bleomycin iron complex.